The importance of wealth effects on pastoral production: A rapid method of wealth ranking - Grandin, B.E. (International Livestock Centre for Africa, 1983)
Discusses the importance of wealth differences among producers in traditional pastoral production systems, describing a rapid method, dependent on informants, for determining the wealth rank of producers within a given community in order to stratify a population of producers before sampling.